Clinical-Statistical Study Regarding The Decay Frequency Of The First Permanent Molars - Liana Beresescu; Mariana Pacurar; Petcu Blanka (Romanian Society of Oral Rehabilitation, 2013)
The aim of this study was to determine the frequency of dental caries developed on the first permanent molars in a group of school children. Materials and methods This screening was performed on a group of 385 children, all pupils in first year at elementary school in Târgu Mureş. For the assessment of the dental health we used DMF index. Results The average value of DMF index (in first permanent molar) was 0.87, with the standard deviation of ±1.01 of the 1526 erupted molars 336 (22.01%) were already affected by caries. Conclusions The index of dental caries intensity obtained in this study and the prevalence of caries have high values similar to those reported in other epidemiological studies.